The Impact of Diclofenac Suppositories on Post-Cesarean Section Pain: A Systematic Literature Review - Sara Agyemang Antwi; Prince Kwabena Agyemang Antwi; Samuel Akwasi Adarkwa; Kwesi Boadu Mensah; Eric Woode (Anesthesiology Research and Practice)
Clinical Implications: Patient satisfaction can be improved with these enhanced pain management strategies. Also, reliance on opioids for postoperative pain management and its related side effects will be reduced. This research reinforces the importance of multimodal analgesia in postoperative pain management. The findings also open pathways for further clinical trials to explore the appropriate combinations, dosages, and administration of NSAIDs for specific surgical populations and settings. Future research should focus on standardizing methodologies and addressing risk of bias to enhance reliability of findings related to diclofenac suppository and multimodal analgesia.